The role of vitamin D and its supplementation in sarcoidosis – current status - Bieda, Anna; Kondracka, Monika; Bielecki, Michał; Zapałowska, Agata; Kondracki, Kamil; Szczepańska, Milena; Kozłowski, Wojciech (Rzeszów University Press, 2025)
Introduction and aim. Sarcoidosis is a chronic autoimmune-related inflammatory disease characterized by non-caseating granuloma formation. The macrophages accumulating in granulomas express increased 1alpha hydroxylase activity. Increased extrarenal 1,25-dihydroxyvitamin D synthesis can lead to hypercalcemia and its complications. However, 25-hydroxyvitamin D deficiency and insufficiency are virtually universal among sarcoidosis patients. The aim of this study was to explain the complex role of vitamin D and to its metabolites and discuss the possible benefits and risks associated with the administration of exogenous vitamin D to patients with sarcoidosis. Material and methods. PubMed and Scopus databases were searched for reviews about The role of vitamin D and its supplementation in sarcoidosis. The authors have analyzed a total of 107 full-text articles published between January 2000 and November 2024, with additional articles identified by bibliography analysis. Analysis of literature. The potential benefits of vitamin D supplementation in sarcoidosis are promising in terms of reducing the inflammatory response, counteracting disease progression, reducing bone fracture risk, and minimizing the pharmacotherapy needed for disease control. However, the risk of hypercalcemia should not be neglected. Conclusion. Despite the increased risk of hypercalcemia, vitamin D supplementation in patients with sarcoidosis should be considered. Each patient’s benefits-to-risks ratio of vitamin D supplementation should be assessed individually and the inter vention should be closely monitored both before and during implementation.
Keywords: bone mineral density; disease course; hypercalcemia; sarcoidosis; supplementation; vitamin D